2017
DOI: 10.2134/jeq2016.06.0220
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Impact of Seasonal and Short‐term Manure Application Decisions on Phosphorus Loss in Surface Runoff

Abstract: Agricultural phosphorus (P) management is a research and policy issue due to P loss from fields and water quality degradation. Better information is needed on the risk of P loss from dairy manure applied in winter or when runoff is imminent. We used the SurPhos computer model and 108 site-years of weather and runoff data to assess the impact of these two practices on dissolved P loss. Model results showed that winter manure application can increase P loss by 2.5 to 3.6 times compared with non-winter applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 38 publications
3
54
0
Order By: Relevance
“…2) under manure treatment were more accurate than those for plots receiving no P fertilization at the same site reported previously (Wang et al, 2018a): DRP losses in surface runoff (<0.4 kg ha −1 ) (NSE of 0.54) and subsurface tile drainage (<0.6 kg ha −1 ) (NSE of 0.58). This is consistent with the finding that a narrow range of DRP loss with relatively low variability would generally result in lower model accuracy (NSE) than those observed for predictions with manure application and a wider range of DRP losses (Vadas et al, 2017). Indeed, manure application increased the range of DRP loss when followed closely by a large rainfall event, thereby typically leading to better accuracy statistics.…”
Section: Resultssupporting
confidence: 89%
“…2) under manure treatment were more accurate than those for plots receiving no P fertilization at the same site reported previously (Wang et al, 2018a): DRP losses in surface runoff (<0.4 kg ha −1 ) (NSE of 0.54) and subsurface tile drainage (<0.6 kg ha −1 ) (NSE of 0.58). This is consistent with the finding that a narrow range of DRP loss with relatively low variability would generally result in lower model accuracy (NSE) than those observed for predictions with manure application and a wider range of DRP losses (Vadas et al, 2017). Indeed, manure application increased the range of DRP loss when followed closely by a large rainfall event, thereby typically leading to better accuracy statistics.…”
Section: Resultssupporting
confidence: 89%
“…S2a and S2b). Vadas et al (2017) also found that nonwinter manure application to fields with medium or high runoff potential resulted in greater dissolved P loss than winter application to low‐runoff fields. Maximum annual P losses simulated in all scenarios demonstrate the potential for major P loads at any time of the year (Table 3).…”
Section: Resultsmentioning
confidence: 84%
“…Winter manure applications, which experience minimal, if any, nutrient crop uptake, often coincide with active transport pathways created by frozen and water‐saturated soils (Fleming and Fraser, 2000; Srinivasan et al, 2006; Williams et al, 2011; Vadas et al, 2017). Due to the resulting high risks for nutrient loss, many countries constrain or even ban winter manure applications (Webb et al, 2012).…”
mentioning
confidence: 99%
“…During modeling research using Eq. [1] to simulate P loss in runoff from winter‐applied manure, Vadas et al (2017) found that field‐scale runoff data also indicated incomplete interaction of snowmelt water with solid beef manure. Clearly, this possibility of incomplete snowmelt water interaction with solid manure and reduced DRP release deserves further investigation, especially as we could find no literature on this topic.…”
Section: Resultsmentioning
confidence: 99%